Pneumococcal Vaccination and Revaccination of Older Adults - Artz, Andrew S. (American Society for Microbiology, 2003)
As individuals advance in age, the risk of infection, bacteremia, and mortality caused by Streptococcus pneumoniae rises. Retrospective data demonstrate that the licensed penumococcal polysaccharide vaccine (PPV) is effective in older persons in reducing serotype-specific invasive disease. PPV demonstrates good immunogenicity in older adults, generally comparable to that in younger subjects, although certain cohorts respond less well. The response to PPV is T cell independent, however, and does not elicit immunologic memory. The duration of the anti-capsular polysaccharide antibody response appears to wane as early as 3 years after vaccination. In older persons, revaccination induces an antibody response, although it may not be as strong as that from the initial vaccine. While revaccination of older adults has been recommended, clinical efficacy has not yet been proven. Measures of antibody function may be at least as important in determining protection as are quantitative antibody levels. Additional studies of immunogenicity, particularly regarding revaccination, will facilitate the design of an optimal pneumococcal vaccination policy. Research into conjugate- and protein-based pneumococcal vaccines, which elicit T-cell-dependent responses and induce immunologic memory, is needed in older persons. In the meantime, administering to PPV to recommended groups should be a public health priority.